Claude Rawson in conversation with Marjorie Perloff. Issue 4 (7th June 2017) - Rawson, Claude; Perloff, Marjorie
PREFACE: Claude Rawson has been called 'perhaps the best living scholar in eighteenth-century satire, and perhaps of British satire itself', and there is frequent reference in the literature to 'Rawson's unassailable pre-eminence as Swift's most challenging, exciting, and erudite modern critic'. In the words of Robert Alter, 'What Rawson bracingly demonstrates is that humanistic inquiry still can be, and deserves to be, an empirically grounded activity'. Before his retirement in 2014, Rawson was the first Maynard Mack Professor of English at Yale, where he had taught since 1986. Before that, he was for many years (1971–1986) professor at the University of Warwick: while at Warwick, he served as Department Chairman and was the co-editor of Modern Language Review . Rawson has held many distinguished visiting professorships around the world, most recently in China, where he was born and grew up. He is the author of numerous now-classic scholarly studies, among them God, Gulliver, and Genocide, and has edited dozens of scholarly editions, individual volumes of essays, and series like the Cambridge History of Literary Criticism. He is currently the general editor of the Cambridge Edition of the Works of Jonathan Swift, now in process. In the 1980s, he was a regular contributor to the London Review of Books, writing on a great variety of literary and cultural topics, and he continues to contribute to the TLS and other periodicals. Since retirement, Rawson spends much of his time in Cambridge. Marjorie Perloff is the Sadie D. Patek Professor of Humanities Emerita at Stanford University. She contributed an essay 'Beckett in the Country of the Houyhnhnms' to the 2008 Cambridge University Press Festschrift for Rawson called Swift's Travels: Eighteenth-Century British Satire and its Legacy . The interview took place via email between Cambridge and Los Angeles, which is Perloff's home, in August-October 2016.